Estrés laboral y desempeño laboral de los empleados del GAD de Chaguarpamba, en la actualidad - Herrera Conza, Olga Viviana (2025)
Job stress is a problem that affects millions of workers around the world, affecting their physical and emotional state; it also has a negative influence on job performance. The main objective of this research is to analyze the incidence of work stress on the work performance of the employees of the Decentralized Autonomous Government (GAD) Chaguarpamba, at present; the specific objectives consisted of conceptualizing the theoretical foundations on work stress and work performance; identifying the relationship between work stress and work performance; and developing an intervention proposal from the perspective of social work as a measure to reduce work stress and improve the work performance of the employees of the GAD Chaguarpamba. Regarding the methodology, the research had a mixed approach, it was also cross-sectional, the technique used was the survey with a test instrument that evaluated job stress and a questionnaire applied to 82 employees that was used to evaluate job performance. The results showed that employees present high levels of emotional exhaustion and depersonalization and low levels of personal fulfillment suggesting the presence of stress and, on the other hand, work performance is affected by stressors. In conclusion, the relationship between stress and work performance in the employees of the GAD of Chaguarpamba was identified, which negatively affects the worker's mental, emotional and physical health and this in turn has repercussions on their work performance, suggesting the need for intervention